The Contribution of Mobile Pastoral Herds to Soil Fertility Maintenance in Sedentary Mixed Crop-Livestock Systems at Farm and Territory Scales—Part of Mutually Reinforcing Social and Ecological Relationships Supporting Sustainability - Alary, Véronique; Aboul-Naga, Adel; Osman, Mona A.; Daoud, Ibrahim; Vayssières, Jonathan (Frontiers in Sustainable Food Systems, 2021)
Agricultural development through settlement schemes on desert lands has always raised acute debates, especially over environmental issues due to cultivation based on intensive additions of water and fertilizers. However, nutrient cycling approaches at the farm level are generally based on apparent N flows, i.e., purchased inputs and sold products, without considering nutrient flows driven by mobile herds crossing the arable lands of sedentary farmers. Through a territory level approach, the present study aimed to assess the contribution of mobile pastoral herds located in the newly reclaimed land on the western desert edge of the Nile Delta on the supply of the manure for local sedentary farms. Based on a survey of 175 farmers, we calculated the partial farm nitrogen balances. Supplemental interviews were conducted with the pastoral community to assess the additional manure coming from grazing practices in the research area. The results show that the sedentary mixed crop-livestock systems based on the planting of Trifolium alexandrinum and a manure supply make a useful contribution towards converting poor, marginal soil into fertile soil. Moreover, grazing of crop residue grazing by pastoral herds on the reclaimed land contributes to social sustainability by maintaining social links between the first occupants, the Bedouins, and the new settlers. Grazing accounts for 9% to 34% of farm-level N input and 25% to 64% of farm-level N output depending on the village and the cropping system. This contribution calls for different rural policies that consider the complementarity between pastoral herders and sedentary farmers that supports both systems' social and environmental sustainability.